THE INVESTIGATION INTO PRIMACY EFFECT ON STUDENT’S VOCABULARY MEMORIZATION - Sabudu, Delli (University of Muhammadiyah Malang, 2019)
This study aimed to examine whether primacy positions are more dominant in memorizing words, in other words, this study intends to test which ones are easier to remember words that are at the top or the beginning or words that are at the bottom or end in the word memorization list. In this study, the authors used a sample of first grade SMP Negeri I students. From a number of parallel classes the author takes the class as a sample. Data collection is done through tests in the form of a post-test. By using the t-test formula, the collected data is then analyzed to test the hypothesis whether there is a significant difference between the two groups of students who memorize the primacy position and the students who memorize the recency position. The experimental group gets a higher number in memorizing words in the primacy position in memorizing vocabulary. By using a two-tailed test, proved that Ho is rejected. For this reason, it is expected that teachers who teach English or other foreign languages can teach vocabulary by placing difficult words on the memorizing list in the top or primary position.